Certificate of authenticity for the lock of Goethe's hair in the framed object in the Yvonne Hummel Collection (C_Hummel_001) - Hummel, Betty, 1793-1883 (scribe):::::::::::::::; Walther, L. (court official)::::::::::::::: (2023)
Certificate of authenticity for a lock of the hair of Johann Wolfgang von Goethe, inscribed by Betty Hummel and certified by L. Walther of the Grand-ducal Saxon Court of Law in Weimar, Feb. 6, 1877.